2005
DOI: 10.1007/s00380-004-0804-6
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin allergy in cancer patients manifesting as Kounis syndrome

Abstract: Two cases of allergic angina and allergic myocardial infarction (Kounis syndrome) following penicillin administration are described. The patients suffered from lung and mandible neoplasms and had previously received several courses of antineoplastic therapy without any sequelae. One patient had normal coronary arteries (type I variant of the syndrome) and the other had coronary artery disease with previous myocardial infarction (type II variant of the syndrome). The allergic reaction following penicillin admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Two of them had developed after taking oral ACA in patients who had normal coronary arteries [8,9]. The third case had progressed after intravenous penicillin use in a cancer patient [7]. All of them were concordant with type-I of KS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two of them had developed after taking oral ACA in patients who had normal coronary arteries [8,9]. The third case had progressed after intravenous penicillin use in a cancer patient [7]. All of them were concordant with type-I of KS.…”
Section: Discussionmentioning
confidence: 96%
“…In previous reports, only three ACA-induced KS cases were reported [7][8][9]. Two of them had developed after taking oral ACA in patients who had normal coronary arteries [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…These favour vasoconstriction, collagen destruction and plaque erosion or rupture, which may trigger an acute coronary syndrome [1,2]. In fact, high levels of histamine have been found in patients with vasospastic angina [4], although no definitive studies have shown a causal relationship between the allergic reaction and the ensuing acute coronary syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently described that the onset of allergic phenomena in predisposed subjects can trigger an angina episode [1,2]. The association of acute coronary syndrome and hypersensitivity reactions has been described as Kounis syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation